Health communication and news framing: Analysis of Chinese television news during the covid-19 pandemic - Zhang Shuang; Lee Kuok Tiung (Scopus, 2024)
This study uses content analysis to examine the information framing and fitness discussion methods used in Chinese language television news during the COVID-19 epidemic. Through a methodical analysis of several television information evaluations, it is well recognized that the media disseminated fitness statistics throughout the epidemic and influenced public perception and actions.